Tips and Trick Pengaturan Keuangan untuk UMKM dalam Mencapai Kesuksesan Level 3 di Kecamatan Bojongloa Kidul Bekerjasama dengan Dinas UMKM Kota Bandung - Kusumawardhani, Aninditha Putri (LPPM UNIBI, 2022)
In the period after the Covid 19 pandemic ended, MSMEs became one of the driving forces of the national economy with their contribution and role in absorbing more labor compared to other business elements in Indonesia. Looking at the problems existing with partners, the solution given is to provide literacy or knowledge in the form of material presentations, discussions, sharing sessions which are carried out offline, including by determining what financial records are carried out and strategies for making existing businesses a provision. long-term.